Scaffolding Based Direct Instruction Strategy in Memorizing Prayer Readings for Students with Mild Mental Retardation - Salasiah; Khamam Khosiin; Khoiriyah (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
This study examines the implementation of scaffolding based direct instruction in prayer recitation memorization for students with mild intellectual disabilities at SMALB Negeri Tanjung Redeb. The study used a qualitative approach with a descriptive case study design. Data were collected through classroom observation, in-depth interviews, and documentation. The findings show that Direct Instruction was implemented through clear teacher modeling, task analysis, guided imitation, structured repetition, immediate correction, visual and auditory media, positive reinforcement, and gradual reduction of teacher support. This strategy helped students memorize prayer recitations in a more structured and meaningful way. The cognitive impact appeared in students’ improved ability to remember short recitation units, arrange recitations in the correct sequence, and reduce dependence on teacher prompts. The affective impact appeared in increased motivation, confidence, enthusiasm, and willingness to participate. The psychomotor impact appeared in clearer pronunciation, better articulation, more orderly prayer movements, and improved coordination between recitation and movement. The success of the strategy was supported by teacher patience, concrete media, school support, rewards, and parental involvement. However, the process was limited by students’ weak memory, short attention span, difficulty pronouncing Arabic words, and inconsistent home practice. The study concludes that scaffolding-based Direct Instruction is an effective, structured, and adaptive strategy for strengthening prayer recitation memorization among students with mild intellectual disabilities.